Machine-learned target volume delineation of 18F-FDG PET images after one cycle of induction chemotherapy. (May 2019) - Parkinson, Craig; Evans, Mererid; Guerrero-Urbano, Teresa; Michaelidou, Andriana; Pike, Lucy; Barrington, Sally; Jayaprakasam, Vetri; Rackley, Thomas; Palaniappan, Nachi; Staffurth, John; Marshall, Christopher; Spezi, Emiliano
Highlights: MTV on 18 F-FDG PET after one cycle of induction chemotherapy have less uptake. MTV on 18 F-FDG PET after one cycle of induction chemotherapy have smaller volumes. Automated MTV delineation is not comparable to manually delineated volumes. Machine-learned MTV delineation is comparable to manually delineated volumes. Abstract: Biological tumour volume (GTVPET ) delineation on 18 F-FDG PET acquired during induction chemotherapy (ICT) is challenging due to the reduced metabolic uptake and volume of the GTVPET . Automatic segmentation algorithms applied to 18 F-FDG PET (PET-AS) imaging have been used for GTVPET delineation on 18 F-FDG PET imaging acquired before ICT. However, their role has not been investigated in 18 F-FDG PET imaging acquired after ICT. In this study we investigate PET-AS techniques, including ATLAAS a machine learned method, for accurate delineation of the GTVPET after ICT. Twenty patients were enrolled onto a prospective phase I study (FiGaRO). PET/CT imaging was acquired at baseline and 3 weeks following 1 cycle of induction chemotherapy. The GTVPET was manually delineated by a nuclear medicine physician and clinical oncologist. The resulting GTVPET was used as the reference contour. The ATLAAS original statistical model was expanded to include images of reduced metabolic activity and the ATLAAS algorithm was re-trained on the new reference dataset. Estimated GTVPET contours were derived using sixteen PET-AS methods and compared to the GTVPET using the Dice Similarity Coefficient (DSC). The mean DSC for ATLAAS, 60% Peak Thresholding (PT60), Adaptive Thresholding (AT) and Watershed Thresholding (WT) was 0.72, 0.61, 0.63 and 0.60 respectively. The GTVPET generated by ATLAAS compared favourably with manually delineated volumes and in comparison, to other PET-AS methods, was more accurate for GTVPET delineation after ICT. ATLAAS would be a feasible method to reduce inter-observer variability in multi-centre trials.